Effect of Time Overruns on Apartment Building among Kuantan Malaysian Construction Industries - Nur A'shirah, Mohd Azman; Adeleke, A. Q. (Penerbit Akademia Baru, 2018)
This paper assessed the effect of time overruns on apartment building among Kuantan Malaysian construction industries. A survey was conducted among 10 construction industries in Kuantan Pahang. Using proportionate stratified random sampling, out of which 10 questionnaires were distributed for data analysis. Using five point Likert scale categories from previous studies, statistical analysis affirmed a significant positive relationship between time over runs and apartment building among Kuantan Malaysian construction industries.